Strategies to ensure intestinal and systemic health of piglets challenged with diets without antibiotics or nutritional deficiency and high density - Chaves, Rhuan Filipe (2022)
The objective of study 1 was to evaluate the effects of organic acids associated with polyphenols on cellular and humoral immune response, morphology, antioxidant capacity in the jejunal mucosa, production of short-chair fatty acids (SCFA) in the cecum and colonic microbiota in weaned piglets. The treatments were: basal diet without antimicrobials additives (NC); basal diet with 120 ppm of halquinol (PC); NC + 0.05% of blend with organic acids associated with polyphenols (OAP1); NC + 0.10% of same blend (OAP2). In the starter II phase (d 28 to 42), the pigs of the PC, and OAP2 treatments showed a greater body weight (BW) and average daily gain (ADG) as well as for the entire period, ADG. The NC pigs had the highest incidence of diarrhea during the starter I phase, regarding the overall period OAP1 had the lowest diarrhea incidence. The OAP2 group reduced the counts of neutrophils. When compared with the NC and PC group, OAP2 supplementation significantly increased the glutathione S-transferase (GST) in the jejunal mucosa. In the microbiome analyses, it was observed that the OAP1 and NC groups had similar colonic microbiota when compared to the PC and OAP2 piglets. A significant increase in the number of operational taxonomic units (OTUs) was observed in the NC group. In conclusion, supplementation with 0.1% of the blend with organic acids associated with polyphenols can replace growth promoting antibiotics and increase jejunal redox parameters, modify the colon microbiome and improve the growth performance of piglets in the nursery phase. The objective of study 2 was to evaluate the replacement of crystalline tryptophan (CTrp) by tryptophan biomass (BTrp) and the effects on growth performance, score fecal, intestinal permeability, redox parameters, immune status, and cortisol of piglets raised at different rearing densities. Two rearing density (0.15 and 0.4 m2/pig) and three diets (without synthetic tryptophan (Trp), CTrp and BTrp) were the factors studied. The body weight was recorded at 0, 8, 14, 28, and 42 days. Fecal scoring was graded as score 1, score 2, and score 3 all the experimental periods. On day 43, blood samples were collected for further laboratory analyses. Piglets that fed CTrp had higher BW, ADFI, and ADG than piglets from the Trp-deficient treatments at all phases. Piglets that fed BTrp had higher BW than the Trp-deficient treatments at 28 and 42 days and ADG from the pre-starter II phase. Piglets that fed BTrp had higher ADFI only in the starter I phase. In the total period, piglets from Trp-deficient treatments had lower ADFI and ADG, and higher FCR than piglets that fed Trp sources. The high rearing density reduced the BW and ADG and increased the FCR from the starter I phase. Only the rearing density factor influenced the fecal score of the treatments. From pre-starter II, and considering the total period, piglets from treatments with high rearing density had a higher percentage of score 1 than piglets that were kept at normal rearing density. From starter II, and considering the total period, a higher percentage of score 2 was observed in treatments with normal rearing density. There was an interaction for the analyzed factors (rearing density and Trp) for the serum cortisol concentration, so that the piglets of HD treatment had higher concentration than piglets of ND treatment, as well as HD+BTrp treatment. There was also interaction for the concentration of IFN-alpha, and the HD+BTrp treatment had a lower concentration than the other treatments, except for the ND+Ctrp treatment. In conclusion, the conventional tryptophan source can be replaced by biomass tryptophan in the nursery phase. Additionally, the use of tryptophan biomass can attenuate the concentrations of stress indicators in animals at high rearing densities.